Correlation between Self Concepts and Peer Social Support with Academic Procrastination: Hubungan Antara Konsep Diri Dan Dukungan Sosial Teman Sebaya Dengan Prokrastinasi Akademik - Rohmah, Lailatul Sifa'ur; Suryanto, Suryanto; Matulessy, Andik (Psikologia : Jurnal Psikologi, 2019)
This study aims to analyze 1) negative correlation between self-concept and academic procrastination, 2) negative correlation between peer social support and academic procrastination, 3) simultaneous negative correlation between self-concept and peer support and academic procrastination. This study uses a quantitative approach. The subjects of this study were 112 students with the same characteristics. The sampling technique used is probability sampling. Data collection was carried out using 3 scales namely academic procrastination scale, self concept scale and peer social support scale. The results showed that: 1) There was a significant negative correlation between self-concept and academic procrastination obtained p value = 0.003, 2) There was no significant negative correlation between social support of peers with academic procrastination obtained p value = 0.481, 3) There was a correlation significant negative simultaneously between self-concept and peer social support with academic procrastination obtained F = 8,535 p = 0,000 with R square = 0,135. Effective contribution of self-concept variables and peer social support with academic procrastination of 13.5%. Students are expected to always learn to think positively in interpreting their lives, being open in expressing their feelings, and interacting with their peers.